Market grooming : the dark side of AI marketing - Dadwal, Sumesh; Jahankhani, Hamid; Revett, Kenneth (Emerald Publishing Limited, 2024)
Market Grooming: The Dark Side of AI Marketing marks a paradigm shift in the field of marketing. This thought-provoking scholarly work examines how customers, markets and communities are groomed, socially conditioned, subliminally marketed to, and influenced by the use of AI technologies. This comprehensive collection of research articles covers various aspects of AI and its impact on marketing, consumer behavior, and market grooming. It delves into the views and attitudes of consumers in the AI era, as well as the negotiation tactics and misbehaviors observed in digital AI marketing. The impact of AI, machine learning, and the Internet of Things on business and marketing models is thoroughly explored, including both positive and negative effects on individuals, communities, and different domains like social, politico-legal, and ethical spheres. The collection further examines customer relationships management (CRM) and the consequences of AI implementation in marketing and market grooming, highlighting the need for anti-data mining practices. Lastly, it addresses the challenges, concerns, and strategic directions for achieving ethic-socio-sustainable marketing using technology, especially in the context of Industry 5.0. With contributions from experts in universities and institutions worldwide, this work offers valuable insights for regulators, marketers, governments, and communities in navigating the ever-evolving landscape of AI-driven marketing and market grooming.